(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
New tetra-dentate Schiff base N’, N”-1, 2-diphenylethane-1, 2-diylidenedibenzohydrazide (1) was synthesized by the condensation of benzil with isonizide. Further ligand (1) was converted into Cu (II) complex with N’, N”-1, 2-diphenylethane-1, 2-diylidenedibenzohydrazide (2) by treatment of (1) with CuCl2.2H2O and in another route Ni (II) complex with N’, N”-1, 2-diphenylethane-1, 2-diylidenedibenzohydrazide (3) was synthesized with reaction of (1) with NiSO4.7H2O. Polarographic studies of Cu (II) and Ni (II) complexes with ligand have been done in alcoholic medium and the stability constant log β values were found for Cu (II) and Ni (II) complexes Ligand and complexes were characterized by IR and 1HNMR, and complexes tested for biological activity.